Left ventricular structural heterogeneity and myocardial remodelling - A. M. Naidich (Бюллетень сибирской медицины, 2006)
Aimed at studying interrelation between left ventricular (LV) structural heterogeneity and myocardial remodeling, we exa- mined a group pf subjects having coronary artery disease (CAD) of several severity degree. Based on three-dimensional reconstruc-tion of LV and using original analysis methods of esophageal ultrasound investigation data, standard parameters of myocardial re-modeling ( mean values of wall thickness and short axis LV radius, interrelations of long and short semi-axes, camera volume, myo-cardial mass and its relation to the wall thickness) were scored. The assessment of heterogeneity in LV regions was performed with space resolution 4x4 mm using parameters which are characteristic of heterogeneity of the wall thickness and curvature degree and also, scale of constitution of connective material by connective tissue. Correlation analysis performed between data of LV remodel-ing and its structural heterogeneity revealed strong correlation events studied in the heart. It proved that the higher myocardial re-modeling degree the lower heterogeneity of LV. It means that myocardial remodeling process in the setting of advancing CAD de-velops to decreased scale of LV structural heterogeneity. It is suggested that heterogeneity in normal heart serves as structural basis for myocardial remodeling.